Políticas de formação de professores: o brasil no contexto da globalização - Chapani, Daisi Teresinha (Góndola, enseñanza y aprendizaje de las ciencias, 2014)
This paper presents some considerations about the current policies of teacher education in Brazil. Considering the context of globalization, we understand that it is possible to make some comparisons with the situation in Colombia. Thus, we will begin discussing the process of globalization, then be treating the current education policies with some actions that occur in Brazil, and we conclude with some critical considerations about such policies.